EFFECT OF WORK STRESS AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE - Anggita Nurjannah; Jasman Sarifuddin (Proceeding International Seminar of Islamic Studies, 2022)
The purpose of this study is to find out and analyze the effect of work stress on employee performance, to find out and analyze the effect of workload on employee performance and to find out and analyze the effect of work stress and work motivation on employee performance at the Perum BULOG Medan Branch Office. The theory used in human resource management research related to work stress, work motivation and employee performance. The approach used in this study is an associative approach. The population in this study was the total employees of Perum BULOG Medan Branch Office which amounted to 36 people and the sample used in this study was the entire population of 36 people. The data collection technique in this study used questionnaires. The data analysis technique in this study uses the Classical Assumption Test, Multiple Linear Regression, t Test and F Test, and coefficient of determination. The data processing in this study uses the SPSS software program (version 25.2020). It is partially known that work stress has a negative and significant influence on employee performance at perum BULOG Medan Branch Office. It is partially known that work motivation has a positive and significant influence on employee performance at Perum BULOG Medan Branch Office. Simultaneously it is known that work stress and work motivation have a significant effect on employee performance of Perum Bulog Medan Branch Office.